Design and Development of a Goods Data Collection Information System at Pt. Pacific Medan Industry with Web-Based CodeIgniter Framework - Purba, Mikael; Harahap , Sahyunan; Irwan , Irwan (Cattleya Darmaya Fortuna, 2024)
Study This aim For designing And build A System Information Data collection Goods (SIPB) addressed special for PT. Pacific Medan Industri . PT. Pacific Medan Industri is moving company​ in field manufacture And distribution goods . System This built with using the CodeIgniter framework as base development , with focus on application web based for facilitate the data collection process goods in a way efficient . Method development system covers analysis needs , design system , implementation , and testing in a way iterative . CodeIgniter Framework chosen Because its reliability in speed up development web applications and provide organized structure .​ It is hoped that this SIPB can increase efficiency in data collection goods , reduce error humans , as well make it easier access And management information related goods at PT. Pacific Medan Industri .